Bactericidal activity of ceftazidime in serum compared with that of ticarcillin combined with amikacin. - Standiford, H C (1984)
We compared the bactericidal activity of serum attained 1 and 6 h after the termination of infusions of either ceftazidime (2 g) or ticarcillin plus amikacin (5 g and 7.5 mg/kg, respectively) in 6 volunteers against a panel of the most common pathogens found in the blood of febrile granulocytopenic cancer patients. Ceftazidime consistently produced significantly higher serum bactericidal titers at both 1 and 6 h against all species of gram-negative bacilli. Its performance against Pseudomonas aeruginosa was especially impressive. The geometric mean titer against this organism was 1:41 at 1 h, contrasted with 1:12 for ticarcillin plus amikacin (P = 0.025). However, for Staphylococcus aureus, the geometric mean serum bactericidal titer of ceftazidime was 1:3.6 at 1 h and undetectable at 6 h. Ceftazidime shows promise as single-agent therapy for serious gram-negative bacillary infections. Whether this promise is fulfilled and whether the observed antistaphylococcal activity is adequate for empiric therapy in infected granulocytopenic patients need further investigation.